Penatalaksanaan Fisioterapi Pada Kasus Osteoarthritis Genu Dextra Di RSUD Hardjono Ponorogo - Rosalina, Yanda; , Sugiono S.Fis.MH.Kes (2015)
Background: Osteoarthritis is a disorder characterized by progressive joint failure in which all structures of the joint have undergone pathologic change. Characterized by the breakdown of cartilage hyaline and growth of osteophytes at the joint. Clinical symptoms found in touch with phase inflammatory synoviaal, pain, joint stiffness, muscle weaknessss quadriceps and limitations range of motion. Signs and symptoms can be fixed with the modalities with Transcutaneus Electrical Nerve Stimulation (TENS), Infra Red (IR), and Therapeutic Exercise. Aims of research: To study about physiotherapy management in reducing pain, increase muscle strength of the flexor and extensor knee dextra, and increase functional activity in the case of Osteoarthritis genu dextra using modalities Transcutaneus Electrical Nerve Stimulation (TENS), Infra Red (IR) and Therapeutic Exercise (Resisted Active Exercise ) Results: After therapy for about six times the obtained results of the assesment of motion pain T0: 5,8 a T6: 4,6, there is no increase in the muscle strength of the flexor and extensor T0: 4 a T6: 4. Conclusion: Transcutaneus Electrical Nerve Stimulation (TENS) and Infra Red (IR) can reduce pain in knee dextra in caused by Osteoarthritis genu dextra. Therapeutic Exercise like Resisted Active Exercise no increase in the muscle strength in caused by Osteoarthritis genu dextra.